ANALISIS SISTEM PENYEDIAAN PEMESANAN DAN PELEKATAN PITA CUKAI MINUMAN MENGANDUNG ETIL ALKOHOL PADA KANTOR PENGAWASAN DAN PELAYANAN BEA CUKAI MANADO - Makalare, Yuliastri; Ilat, Ventje; Pusung, Rudy (Universitas Sam Ratulangi, 2017)
Excise is a state levy imposed on certain goods which have properties or characteristics established in law. In 2013 the Ministry of Finance of the Directorate General of Customs and Excise changed the monitoring system to MMEA which is to change the way of excise tax from payment to sticking the excise tape by issuing the provisions on sticking the excise band against MMEA. The purpose of this study is to find out whether the MMEA customs declaration, ordering and sticking procedure is in conformity with the prevailing regulations and whether the MMEA monitoring system that has changed can improve the monitoring of MMEA. The analytical method used is descriptive describing the procedure of service provision, ordering, and sticking of excise band of MMEA. The results show that the procedures applied are in accordance with the rules that apply although still have some obstacles in terms of implementation and supervision. Approximately 6,924 bottles of MMEA have no production license, no excise band, using fake excise bands, using used excise tape, using excise duty tape, using excise tape which is incompatible with the type and class and making MMEA containing hazardous materials For humans. Therefore it is expected KPPBC Manado City maximizes the implementation of supervision and control system in force. Keywords: Keywords: sticking Excise tape, MMEA, Supervision.